The Influence of Discounts on the Shopee E-Commerce Platform and Financial Discipline on Impulse Buying Behavior - Peter G. Narsico; Ira Faye N. Apay; Hyacinth P. Belacho; Trisha Ann L. Lawas; Trisia Amor Pangan; Conielyn A. Ronato; Jubail Sebastian Villafor; Lalaine O. Narsico (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The current study examined the nexus between Shopee online discount strategies and impulsive buying behavior among university students, with financial discipline explored as a potential moderator. More prevalent are flash sales, vouchers and gamified promotions in online shopping platforms that can induce impulsive buying behavior, especially among young people. A quantitative descriptive-correlational design was used with a structured survey questionnaire to 456 university students in Cebu City. The questionnaire measured three constructs quantitatively; exposure to Shopee discount, tendency to buy impulsively and financial discipline. Hierarchical multiple regression was used to test the direct effects of Shopee discount exposure, financial discipline, and the interaction of the two on impulse buying behavior. The results indicated that exposure to online discount of Shopee significantly predicted impulsive buying tendency (B = 0.41, p<.001) with about 15% of variance. The final model, which included financial discipline, their interaction and online discount exposure from Shopee, explained about 20.6% of the variance. Discount exposure was still positively associated with impulsive buying tendency (B=0.45, p<.001) and financial discipline had a significant negative association (B=−0.33, p<.001). However, the interaction term between mean-centered discount exposure and financial discipline scores was not statistically significant (B = −0.05, *p* = 0.518). Thus, financial discipline was related to lower impulsive buying tendency in general, but it did not significantly moderate the relationship between the exposure to online discount on Shopee and impulsive buying tendency. Future research should examine other possible moderators and interventions to improve financial self-regulation.